2016
DOI: 10.1161/jaha.115.003154
|View full text |Cite
|
Sign up to set email alerts
|

High‐Fat‐Diet Intake Enhances Cerebral Amyloid Angiopathy and Cognitive Impairment in a Mouse Model of Alzheimer's Disease, Independently of Metabolic Disorders

Abstract: BackgroundThe high‐fat Western diet is postulated to be associated with the onset and progression of Alzheimer's disease (AD). However, the role of high‐fat‐diet consumption in AD pathology is unknown. This study was undertaken to examine the role of high‐fat‐diet intake in AD.Methods and Results5XFAD mice, a useful mouse model of AD, and control wild‐type mice were fed (1) high‐fat diet or (2) control diet for 10 weeks. The effects on cerebral AD pathology, cognitive function, and metabolic parameters were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
66
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 52 publications
(114 reference statements)
6
66
0
1
Order By: Relevance
“…In the present study, we used 5XFAD mice because 5XFAD mice recapitulate major features of AD pathology and are regarded as 1 of the popular models of AD. [18][19][20]27 To examine spatial learning and memory function of 5XFAD mice, we used the Morris water maze test because it is the most popular behavioral assay for detecting AD-relevant cognitive impairments across species. 36,37 We found that 5XFAD mice were more prone to angiotensin II-induced cognitive impairment than control mice, as evidenced by the findings of the water maze test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we used 5XFAD mice because 5XFAD mice recapitulate major features of AD pathology and are regarded as 1 of the popular models of AD. [18][19][20]27 To examine spatial learning and memory function of 5XFAD mice, we used the Morris water maze test because it is the most popular behavioral assay for detecting AD-relevant cognitive impairments across species. 36,37 We found that 5XFAD mice were more prone to angiotensin II-induced cognitive impairment than control mice, as evidenced by the findings of the water maze test.…”
Section: Discussionmentioning
confidence: 99%
“…To assess spatial learning and memory function, from 21 to 25 days after the start of ICV infusion, the Morris water maze test was performed according to our previous protocol. 27 Briefly, swimming paths were video-tracked with a camera fixed on the ceiling of the room and analyzed by the software (Muromachi Kikai, Tokyo, Japan). On the hidden test, the mice had 4 sessions per day on the following 4 consecutive days (days 1 to 4).…”
Section: Morris Water Maze Testmentioning
confidence: 99%
“…Aldehyde dehydrogenase 2 mice are also called HNE mice because they exhibit a greater‐than‐normal hippocampus concentration of the peroxidation product HNE (the earliest evidence for oxidative stress in patients with prodromal AD (30), together with spatial learning and memory impairments and age‐dependent spontaneous AD‐like histopathology (17). 5xFAD mice are a common β‐amyloidogenic model of familial AD that demonstrates hippocampus oxidative stress (including HNE accumulation) and spatial cognitive defects (26, 28). UBE3A ‐knockout mice are a model of AS, a genetic neurodevelopmental disorder characterized by hippocampus oxidative stress and impaired goal location based on external cues and other endophenotypes consistent with that in patients with AS (2, 31).…”
mentioning
confidence: 99%
“…We evaluated Quest MRI during sustained superoxide production from the xanthine/xanthine oxidase reaction (23, 24). We provide proof-of-concept data that Quest MRI can be applied to evaluate hippocampus subfields in vivo in 3 disease models: aldehyde dehydrogenase 2-knockout mice, 5xFAD mice, and UBE3A-knockout mice (25)(26)(27)(28)(29). Aldehyde dehydrogenase 2 mice are also called HNE mice because they exhibit a greater-than-normal hippocampus concentration of the peroxidation product HNE (the earliest evidence for oxidative stress in patients with prodromal AD (30), together with spatial learning and memory impairments and age-dependent spontaneous AD-like histopathology (17).…”
mentioning
confidence: 99%
“…Currently, there are many preclinical animal models with AD‐like pathology. Among them, 5XFAD (5X) mice exhibit overexpression of the human amyloid precursor protein (APP695) with the Swedish (K670N, M671L), Florida (I716V), and London (V717I) familial AD mutations, together with mutant human presenilin‐1 (M146L, L286V) under control of the murine Thy‐1 promoter (Lin et al, ; Oakley et al, ). These mice display significantly accumulated Aβ 1‐42 deposition in their brain parenchyma and develop progressive cognitive impairment with age (Oakley et al, ; Webster, Bachstetter, Nelson, Schmitt, & Eldik, ).…”
Section: Introductionmentioning
confidence: 99%